Multiple sclerosis and exercise—A disease-modifying intervention of mice or men? - Martin, Sarah-Jane; Schneider, Raphael (Frontiers in Neurology, 2023)
Research suggests that physical exercise can promote an anti-inflammatory and neuroprotective state. If so, increasing or optimizing exercise could be considered a 'disease-modifying intervention' in neuroinflammatory diseases, such as multiple sclerosis (MS). Exercise intervention studies conducted in animal models of MS are promising. Various aerobic and strength training regimes have been shown to delay disease onset and to reduce both the clinical and pathological disease severity in mice. However, fundamental differences between the physiology of animals and humans, the disease states studied, and the timing of exercise intervention are significant. In animal models of MS, most exercise interventions begin before disease initiation and before any clinical sign of disease. In contrast, studies in humans recruit participants on average nearly a decade after diagnosis and often once disability is established. If, as is thought to be the case for disease-modifying treatments, the immunomodulatory effect of exercise decreases with advancing disease duration, current studies may therefore fail to detect the true disease-modifying potential. Clinical studies in early disease cohorts are needed to determine the role of exercise as a disease-modifying intervention for people with MS.